A nickel–iridium alloy as an efficient heterogeneous catalyst for hydrogenation of olefins. Issue 71 (15th August 2019) - Bai, Jia-qi; Tamura, Masazumi; Nakagawa, Yoshinao; Tomishige, Keiichi
Abstract : Nickel and iridium supported on SiO2 (Ni–Ir/SiO2 ) acted as an effective and reusable heterogeneous catalyst for hydrogenation of olefins, and it showed higher activity and selectivity than the monometallic counterparts. Abstract : Nickel and iridium supported on SiO2 (Ni–Ir/SiO2 ) acted as an effective and reusable heterogeneous catalyst for hydrogenation of olefins, and it showed higher activity and selectivity than the monometallic counterparts. The Ni–Ir/SiO2 catalyst has small Ni–Ir alloy and monometallic Ni particles, and the high catalytic performance can be attributed to the isolated Ni atom in the Ni–Ir alloys.